Uses of the Past in Iberic Societies: Presenteeism and Memory Prosthesis (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Based on a theoretical approach on “memorial culture”, which characterizes contemporary societies of the end of the twentieth century, this article proposes a comparative analysis of Portuguese and Spanish phases of public memory. The specificities of each case’s respective processes of democratization are important to explain the subsequent construction of memorial discourse in the public sphere: the Portuguese revolutionary upheaval on April 25, 1974; the precedent of the Spanish civil war (1936-39), which has had an influence on the main aspects of the Spanish transition to democracy.
Keywords: Public Memory; Historical Revisionism; 1974 Portuguese Revolution; Carnation Revolution; Spanish Transition to Democracy